The Synergy of Customary Criminal Law and National Criminal Law: Orientation Towards Criminal Law Pluralism - Kukuh Dwi Kurniawan; Yaris Adhial Fajrin; Ade Sathya Sanathana Ishwara (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The synergy between customary criminal law and national criminal law is an important orientation in criminal law reform. This can be seen from the substance of the New Criminal Code which emphasizes the importance of acknowledging the existence of customary criminal law so that aspects of legal pluralism are implemented. This study aims to analyze aspects of the notion of pluralism of criminal law in Indonesia as well as to describe the new orientation of Indonesian criminal law which emphasizes the synergy between customary criminal law and national criminal law. This research is a juridical-normative legal research using a conceptual and statutory approach. The results of the study confirm that the development of the idea of legal pluralism in Indonesia has implicitly been going on for a long time and has even been discussed in a limited way at the BPUPK-PPKI session. After the ratification of the New Criminal Code, the idea of criminal law pluralism has increasingly come to the fore by providing recognition of customary criminal law which emphasizes that after the passage of the New Criminal Code there has been a change in the orientation of legal pluralism which leads to aspects of public law, namely criminal law pluralism. orientation and synergy between national criminal law and customary criminal law based on legal pluralism also requires synergy and precise division of tasks between national law enforcement officials and customary law enforcement officials